Subtitusi Tepung Ubi Jalar Ungu (Ipomoea batatas L.) Dalam Pembuatan Mantau Dengan Penambahan Tepung Beras Merah (Oryza nivara) - Riskha Nur Oktaviani (Politeknik Negeri Ketapang, 2025)
Mantau generally contains a lot of carbohydrates. To add nutritional value to mantau, one of them is by adding purple sweet potato flour and brown rice flour which is quite rich in fiber and antioxidants. This study aims to determine the effect of substitution of purple sweet potato flour with different concentrations in making mantau on its physicochemical properties. This study used an experimental method in the laboratory with the design of a RAK experiment. Sensory testing found that the higher the concentration of purple sweet potato flour added, the more the panelists liked with treatment P4 being the most acceptable on average. Testing the moisture content and expandability produced data that the higher the concentration added, the moisture content and expandability decreased. The lowest moisture content and expandability were found in treatment P1, which were 29.48% and 52.16%, respectively. These results indicate that the addition of purple sweet potato flour has a significant effect on the physicochemical properties of mantau.